Estudo das atividades citotóxica e antitumoral de vitafisilinas isoladas de Acnistus arborescens - Rocha, Danilo Damasceno (2008)
Withaphysalins are C28-steroidal lactones structurally based on the ergostane skeleton commonly found in Solanaceae species. In order to evaluate the anticancer properties of these compounds, five withaphysalins [O, F, M, N and (17S,20R,22R)-5β,6β: 18,20-diepoxy-4β,18-dihydroxy-1-oxowitha-24-enolide] isolated from Acnistus arborescens, a plant from the northeastern Brazilian flora, were analyzed in several biological models. All five withaphysalins showed cytotoxic effects against tumor cell lines, being withaphysalin O the most potent and withaphysalin (17S,20R,22R)-5β,6β: 18,20-diepoxy-4β,18-dihydroxy-1-oxowitha-24-enolide, the less potent. Based on these results, its shown that a double-bond between carbons 2 and 3 is essential for the cytotoxic activity of withaphysalins. Withaphysalins (O, F and N) did not show any specificity to tumor cell lines, showing similar cytotoxic and genotoxic effects against leukemic cells (HL-60) and normal cells (PBMC). Cell viability and growth curves of HL-60 and K-562 treated cells were determined using trypan blue exclusion assay, where all withaphysalins reduced the number of viable cells in a dose-and time-dependent fashion, with IC50 values ranging from 0.7 to 3.5 μM after 72 h of incubation. In HL-60 and K-562 cells, the withaphysalins inhibited DNA synthesis, induced morphological alterations, typical of apoptosis, and only in the HL-60 cell line, and they induced activation of caspase-3. Moreover, it was performed the analyzes of cell membrane integrity, cell cycle distribution, DNA fragmentation and the mitochondrial membrane potential using flow citometry. In these experiments, withaphysalins O and F, only at concentration of 10µM, reduced the number of viable cells to 60 and 40% respectively. In the cell cycle analysis, both withaphysalins led to a cell cycle arrest at G2/M, at the concentration of 5μM. Cells treated with both withaphysalins also showed a significant increase in DNA fragmentation when compared to the negative control. Results of the mitochondrial transmembrane potential showed depolarization changes in accordance to the tested concentration (2.5, 5 and 10μg/mL) with 4.7, 17.5 and 9.1% for withaphysalin O and 7.6, 16.6 and 5.6% for withaphysalin F, respectively. The in vivo antitumor effects of withaphysalin F was performed in animals bearing the sarcoma 180 tumor, and at the highest dose tested (20mg/Kg/day), growth tumor was inhibited in 77%. Histopatological analysis of mice organs showed that withaphysalin F causes moderate toxic effects mostly in liver and kidney, but they may be considered reversible effects. Taking in account all these data, it can be concluded that withaphysalins could be considered as an emerging class of new anticancer compounds.